Analysis of Factors Affecting the Financial Performance of MSMEs in the Culinary Sector in Makassar City - Intan Permata Sari. R; Muhammad Azis; Abd Rahim (LP2M IAIN Palopo, 2025)
This study aims to analyze the factors that influence the financial performance of culinary sector MSMEs in Makassar City. The variables used in this study include Financial Literacy, Financial Management, Access to Capital, Product Innovation, Payment Gateway, Age of Business Actors, Length of Formal Education, Business Experience, and dummy variables to differentiate MSME scale categories (micro, small, and medium enterprises). The study population includes all 9,479 culinary sector MSMEs in Makassar City, with sampling using proportional stratified random sampling techniques to obtain 99 respondents. Data collection was carried out through documentation, questionnaires, and direct observation of business actors. Data analysis methods include descriptive percentage analysis, instrument testing (validity and reliability), classical assumption testing (heteroscedasticity and multicollinearity), multiple linear regression analysis, dummy variable testing, and hypothesis testing using the F test, coefficient of determination (R²), and t test. The study uses quantitative methods. The results of the study showed that the coefficient of determination (R²) value was 0.826, indicating that 82.6% of the variation in MSME financial performance could be explained by the independent variables in the model. The F test produced a calculated F value of 47.524, which was greater than the F table of 2.05, so the research model was declared significant simultaneously. Meanwhile, the results of the t test showed that all independent variables had a significant influence on financial performance because the calculated t value was greater than the t table (1.987). The dummy variable test showed that micro businesses had a lower influence on financial performance compared to small businesses, while small businesses showed a more significant and better influence than medium businesses. The results of this study indicate that business scale also determines the variation in financial performance of culinary MSMEs in Makassar City. Keywords: financial literacy, payment gateway, financial performance, culinary MSMEs, Makassar